70.2k views
1 vote
Solve the following system by graphing x + y - 6= 0 x- y = 0

User Asawyer
by
4.8k points

2 Answers

4 votes

Answer:

Explanation:

y=6-x first equation

y=x for the second

Solve the following system by graphing x + y - 6= 0 x- y = 0-example-1
User Asgoth
by
5.6k points
6 votes

Answer:

(3,3)

Explanation:

x + y - 6= 0

x- y = 0

Add the two equations together

x + y - 6= 0

x- y = 0

-------------------

2x - 6 = 0

Add 6 to each side

2x-6+6 = 0

2x = 6

Divide by 2

2x/2 = 6/2

x = 3

Now find y

x-y = 0

3 - y = 0

y = 3

Solve the following system by graphing x + y - 6= 0 x- y = 0-example-1
User Nishant Ghodke
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.